De-Escalation of Treatment With Oral P2Y12 Receptor Inhibitors: Current Status and Perspectives. (July 2019) - Alexopoulos, Dimitrios; Lianos, Ioannis; Vlachakis, Panagiotis; Sfantou, Danai; Dragona, Vassiliki-Maria; Varlamos, Charalambos
In patients with an acute coronary syndrome undergoing percutaneous coronary intervention, novel P2Y12 receptor inhibitors, prasugrel and ticagrelor, are proposed as "first-line" antiplatelet agents in the absence of contraindications and up to a year from the index event. However, de-escalation of treatment to clopidogrel occurs with a variable frequency in real-life practice, most commonly due to an increased bleeding potential, more frequent side effects, and a higher cost for the novel agents. Pharmacodynamic studies provide most of the data on guidance for de-escalation. Despite positive messages from recent trials and registries, lack of definitive efficacy or safety results of such a strategy remains an obstacle to suggest de-escalation in a routine basis. Carefully designed studies are likely to improve our understanding of the impact of de-escalation and help to better define its position in current pharmacotherapy.